Remnant oral biofilm and microorganisms after autoclaving sterilization of retrieved healing abutments. (24th December 2020) - Barreiros, Pedro; Braga, João; Faria‐Almeida, Ricardo; Coelho, Cristina; Teughels, Wim; Souza, Júlio C. M.
Abstract: Objective: The purpose of this study was to evaluate the sterilization effectiveness against biofilms on retrieved healing abutments used in implant dentistry. Background: A large number of clinicians reuse healing abutments to decrease treatment costs although it can promote infection due to the presence of remnant biofilm biomass. Methods: One hundred and eighty‐five titanium healing abutments previously used for 3 months in oral cavity were assessed in this study. Abutments were submitted to cleaning, chemical disinfection, and autoclave sterilization according to clinical guidelines. The abutments were aseptically placed into glass tubes containing specific bacterial growth medium and then incubated for 10 days. From glass tubes with bacterial growth, 100 µl medium was transferred to Schaedler's agar for morphological identification and counting of strict anaerobes and to Columbia blood agar for presumptive identification of facultative anaerobes after incubation. Isolated strains were then identified at species level by enzymatic and biochemical tests within API microorganism detection platform. Also, polymerase chain reaction (PCR) was performed for identification of undefined strains. Results: After the standard cleaning and sterilization procedures, fifty‐six (approximately 30%) retrieved abutments showed the presence of remnant biofilm biomass. The bacteria identified into the remnant biofilms covering the abutments were representative of the commensal oral microbiota including Aggregatibacter actinomycetemcomitans, Prevotella intermedia, and Enterococcus faecalis . Conclusion: Although some healing abutments did not reveal the existence of bacteria, organic components from biofilm biomass are still strongly adhered on the retentive micro‐regions and surfaces of abutments and therefore that would support the accumulation of biofilm including pathogenic species leading to patients' cross‐infections. Further studies should be performed on the assessment of different materials, design, and connections of the healing abutments associated with clinical disinfection procedures in implant dentistry.